2011
DOI: 10.1080/09540121.2010.541416
|View full text |Cite
|
Sign up to set email alerts
|

Operational challenges in delivering CD4 diagnostics in sub-Saharan Africa

Abstract: Access to reliable and low cost CD4 T-cell enumeration to stage illness and monitor anti-retroviral therapy remains elusive in resource-limited settings. We report challenges in delivering CD4 testing using the microcapillary Fluorescence-Activated Cell Sorter (FACS) methodology (Guava EasyCD4 instrument Guava Technologies, Hayward) in Burkina Faso and Zimbabwe. Resources, instruments, reagents, and training were provided to local laboratories within the existing infrastructure and data on CD4 were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…Thairu et al also confirmed our results about maintenance and reagent stock management, in their study in Burkina Faso and Zimbabwe [26]. A frequently-cited barrier to expansion of EID programs is the cost of the required laboratory assays.…”
Section: Discussionsupporting
confidence: 83%
“…Thairu et al also confirmed our results about maintenance and reagent stock management, in their study in Burkina Faso and Zimbabwe [26]. A frequently-cited barrier to expansion of EID programs is the cost of the required laboratory assays.…”
Section: Discussionsupporting
confidence: 83%
“…Having baseline and one-year values for every child likely would have enhanced our ability to identify the highest-risk patients at their baseline clinic visit. However, these laboratory indicators are unavailable in many low-income regions; 29 thus, addition of these laboratory parameters would limit the utility of more complex predictive models in similar settings in Africa. Our study also revealed aspects of the HIV care program that could be improved.…”
Section: Discussionmentioning
confidence: 99%
“…For this analysis, we examined additional variations in test sensitivity, specificity, testing rates, and result-return rates for the POC strategy, as well as antenatal and postnatal loss to follow-up (LTFU) rates, breastfeeding duration, healthcare and medication costs, MTCT risks, and the discount rate for both POC and laboratory strategies (S1 Table). We also examined both decreased POC CD4 costs, reflecting new POC assays in development, and increased POC CD4 costs, to incorporate possible costs not captured in the base-case estimate, for example: additional healthcare worker time to process CD4 specimens, undergo training, or conduct quality control activities; or reduction in staff capacity to perform other patient-related activities [21,48–50]. Finally, we conducted multiway sensitivity analyses, varying POC assay cost, sensitivity, testing rates, and result return rates simultaneously.…”
Section: Methodsmentioning
confidence: 99%